Scientifically Designed Teacher Education : Teacher Educators’ Perceptions in Norway and Finland - Aspfors, Jessica; Eklund, Gunilla; Holand, Anna; Fiskum, Tove; Hansén, Sven-Erik; Jegstad, Kirsti (Nordic Journal of Comparative and International Education (NJCIE), 2021)
This paper investigates teacher educators’ perceptions of scientifically designed teacher education in Finland and Norway and asks the following research questions: How do teacher educators in Finland and Norway perceive scientifically designed teacher education? How do they perceive teacher education regarding the research-led, research-tutored, research-based, and research-oriented dimensions? The study is comparative and uses a quantitative methodological approach based on a questionnaire survey administered to teacher educators in three departments of teacher education, two in Norway and one in Finland. The findings indicate overall positive and quite similar perceptions between the two countries. Despite the similarities, there were differences, particularly in the dimension concerning teacher-focused activities and in the research-tutored dimension. Furthermore, teacher educators’ perceptions were more varied among the Norwegian teacher educators, compared to the Finnish respondents.